Internal Governance Mechanisms and Operational Performance: Evidence from Index Mutual Funds - Adams, John C.; Mansi, Sattar A.; Nishikawa, Takeshi (Review of Financial Studies, 2010)
We provide new evidence linking board characteristics and performance. We employ a sample of index funds to isolate the operational component of performance, thereby minimizing investment policy effects in our performance measures. Using manually collected governance data from the mutual fund industry covering the period from 1998 to 2007, we find an inverse relation between board size and fund performance. We also find evidence supporting our hypotheses that organizational form (whether the fund sponsor is publicly or privately held) plays an important role in determining operational performance. Specifically, we find that board size, the presence of fund sponsor officers, and boards comprised of all independent directors are related to operational performance when the sponsor is publicly held. For privately held firms, board structure is insignificantly related to performance. Overall, the results are consistent with the notion that there may not be a single optimal board structure that is applicable to all funds, attempts to regulate board attributes should be considered with caution, and sponsor level factors are important board structure considerations. (JLE G34, G32, G20)